Spironolactone is an effective and well tolerated systemic antiandrogen therapy for Hirsute women. - Barth, J; Cherry, C; Wojnarowska, F; Dawber, R (1989)
We treated 22 hirsute women with spironolactone in an open trial to determine whether it caused objective changes in hair growth. Among them, 18 women completed 12 months therapy with 200 mg spironolactone daily. During this period, the mean daily linear growth rates of hair on the face, abdomen, and thigh were reduced to 66% (P less than 0.001), 75% (P less than 0.01), and 72% (P less than 0.001) of their pretreatment values. The mean hair shaft diameters were reduced to 83% (P less than 0.01) on the face, 88% (P less than 0.001) on the arm, 74% (P less than 0.01) on the abdomen, and 80% (P less than 0.001) on the thigh. Daily hair volume production was calculated from the diameter and daily growth rate; it was reduced to 60% (P less than 0.01) on the face, 52% (P less than 0.01) on the arm, 34% (P less than 0.001) on the abdomen, and 48% (P less than 0.001) on the thigh. Six of the 18 women who completed the study developed midcycle vaginal bleeding, and 3 women had previously irregular menstrual cycles regulated. We conclude that spironolactone is effective and well tolerated for hirsute women.